Self antigens expressed by solid tumors Do not efficiently stimulate naive or activated T cells: implications for immunotherapy. - Speiser, D; Miranda, R; Zakarian, A; Bachmann, M; McKall-Faienza, K; Odermatt, B; Hanahan, D; Zinkernagel, R; Ohashi, P (1997)
Induction and maintenance of cytotoxic T lymphocyte (CTL) activity specific for a primary endogenous tumor was investigated in vivo. The simian virus 40 T antigen (Tag) expressed under the control of the rat insulin promoter (RIP) induced pancreatic beta-cell tumors producing insulin, causing progressive hypoglycemia. As an endogenous tumor antigen, the lymphocytic choriomeningitis virus (LCMV) glycoprotein (GP) was introduced also under the control of the RIP. No significant spontaneous CTL activation against GP was observed. However, LCMV infection induced an antitumor CTL response which efficiently reduced the tumor mass, resulting in temporarily normalized blood glucose levels and prolonged survival of double transgenic RIP(GP x Tag2) mice (137 +/- 18 d) as opposed to control RIP-Tag2 mice (88 +/- 8 d). Surprisingly, the tumor-specific CTL response was not sustained despite the facts that the tumor cells continued to express MHC class I and LCMV-GP-specific CTLs were present and not tolerized. Subsequent adoptive transfer of virus activated spleen cells into RIP(GP x Tag2) mice further prolonged survival (168 +/- 11 d), demonstrating continued expression of the LCMV-GP tumor antigen and MHC class I. The data show that the tumor did not spontaneously induce or maintain an activated CTL response, revealing a profound lack of immunogenicity in vivo. Therefore, repetitive immunizations are necessary for prolonged antitumor immunotherapy. In addition, the data suggest that the risk for induction of chronic autoimmune diseases is limited, which may encourage immunotherapy against antigens selectively but not exclusively expressed by the tumor.